Pengaruh Pemberian Kompres Hangat terhadap Penurunan Intensitas Nyeri pada Pasien Gastritis: Studi Kasus - Asisha Muharromah Melanisa; Dyah Rivani; Nita Sritunjung (Pusat riset dan Inovasi Nasional, 2026)
Gastritis is an inflammation of the gastric mucosa that often causes pain in the epigastric area, which can reduce patient comfort and quality of life. This condition requires treatment that is not only pharmacological, but can also be supported by non-pharmacological interventions such as warm compresses that function to provide a relaxing effect and improve blood circulation. This study aims to determine the effect of warm compresses on reducing pain intensity in gastritis patients. The research method used was descriptive with a case study approach on one patient treated in the inpatient ward. Data collection was carried out through interviews, observation, and documentation using the PQRST method to assess pain. The intervention in the form of warm compresses was given for three days with a frequency of once a day for ± 15–20 minutes in the epigastric area. The results showed a gradual decrease in pain intensity from a scale of 6 to a scale of 2 after the intervention, as well as an increase in patient comfort. The implications of this study indicate that warm compresses can be used as an effective, safe, and easy-to-implement independent nursing intervention to help reduce pain in gastritis patients and improve the quality of nursing care.